Moment of reckoning: imagined death and its consequences in late ancient Christianity - Muehlberger, Ellen (Oxford University Press, 2019)
Looking toward death in late ancient Christianity -- The trugh to be found in death : early fourth-century histories -- Creating the experience of death in late ancient sermons -- Training for death : rhetorical formation and the cast of the early Christian imagination -- What remains? Situating the postmortal -- Considering compulsion in late ancient Christianity -- Claiming the future.